Rancang Bangun Sistem Monitoring Proses Produksi Bioetanol Berbasis ESP8266 dan ESP32 SoC: Design and Construction of a Bioethanol Production Process Monitoring System Based on ESP8266 and ESP32 SoC - Afianah, Nuzula; Qanitah, Qanitah; Febriani, Siti Diah Ayu; Susmiati, Yuana (Elektriese: Jurnal Sains dan Teknologi Elektro, 2025)
The increasing demand for renewable energy has driven the development of bioethanol as an alternative fuel to replace or blend with fossil fuels, offering high prospects in the future. Driven by these high prospects, bioethanol production has begun to be widely carried out. However, the bioethanol production process tends to be complex, including fermentation and distillation processes that require intense and strict monitoring. Monitoring of both processes consists of essential parameters that must be considered, such as temperature, pH, and ethanol content, as time series data is taken intermittently and continuously. This monitoring or supervision determines the quality and success of the bioethanol production process from biomass materials, in this case, using fermented and distilled sugarcane juice. This study aims to design and implement a bioethanol production process monitoring system based on the ESP8266 microcontroller and ESP32 SoC. Both micro modules are implemented in a hybrid with HTTP communication for data logger output on a cloud service. This system uses a DS18B20 temperature sensor, a pH sensor, and an MQ3 ethanol gas sensor programmed using the Arduino IDE. The development method used is the waterfall method. Several stages include needs, including system design, implementation, hardware and software testing, and system maintenance. The implementation results show success and satisfactory achievements from the performance analysis of the sensors used. The system can monitor parameters with low errors, <1% at temperature, <10% at pH, and can detect alcohol content up to 96% of the bioethanol produced.